Persons and Pronouns: Exploring Clitics in Judeo-Spanish - Naomi Kurtz (Isogloss, 2022)
Optional versus obligatory clitic doubling and the person-case constraint (PCC) repair constitute two puzzles researchers haven’t fully addressed. In Judeo-Spanish, doubling is obligatory for third person accusative strong pronouns; for all other arguments, doubling is optional. This analysis contends arguments are generated with corresponding clitics in the syntax. The realization of clitics is regulated by functional heads: v and X, a head located beneath v. X is hypothesized to be a probe specified only for person; critically, third person accusative strong pronouns lack person features (Anagnostopoulou 2003), while other arguments bear person features. Optional doubling is regulated by alternations in Agree with v or X. An argument that appears without a co-referring clitic is derived via agreement with X. This interaction triggers deletion of clitics’ phi-features, which causes them to be null. Overt cliticization is derived via agreement with v. Obligatory doubling is derived via Agree strictly with v; third person accusative strong pronouns cannot be potential goals for X since they lack person features. Apart from doubling, X generates the PCC repair by blocking Agree between v and dative clitics, causing dative arguments to appear without a matching clitic, and by eliminating intervention effects between v and accusative clitics